PENDIDIKAN KARAKTER DALAM PERSPEKTIF ISLAM (KAJIAN PENERAPAN PENDIDIKAN KARAKTER DI LEMBAGA PENDIDIKAN ISLAM) - Asmaun Sahlan (el-hikmah, 2012)
Character building is an urgent need for Indonesia, specifically in improving the characters of current youth. Character education in the Islamic perspective equate as moral. As Holy Qur'an being the foundation of Islam in all areas of life including on the question of morality; God in His Word, which means "And truly you are (Muhammad) of noble character." Therefore it may also be concluded that Prophet Muhammad, was sent to earth no other but to meliorate the human kind. Thus, the character education in the Islamic perspective is necessary, especially in Islamic educational institutions. Hence, from a variety of issues related to morality, the Islamic educational institutions are ideally capable of implementing the character education within perspective of Islam in the form of honesty, a sense of responsibility, intelligence improvement, with attention to health and hygiene, as well as awareness and creativity.